Long-term survival and late toxicities of elderly nasopharyngeal carcinoma (NPC) patients treated by high-total- and fractionated-dose simultaneous modulated accelerated radiotherapy with or without chemotherapy. (February 2019) - Miao, Jingjing; Wang, Lin; Zhu, Manyi; Xiao, Weiwei; Wu, Haijun; Di, Muping; Huang, Yuqing; Huang, Shaomin; Han, Fei; Deng, Xiaowu; Guo, Xiang; Zhao, Chong
Highlights: High-dose IMRT greatly improved local control and outcomes in elderly NPC patients. No grade 4 toxicities were observed, except for acute haematologic toxicities. CCRT did not seem to improve long-term survival of stage II–IVb elderly NPC patients.